Development Strategies An-Nur Penatar Sewu Islamic Boarding School - Murni Nikmatillah; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study aims to analyze coaching strategies in the midst of the covid 19 pandemic. This study uses a qualitative method that relies on data obtained by researchers from interviews and recordings made in natural settings. This research was conducted at the An-nur Penatarsewu Islamic boarding school which examined the history of the formation of the cottage, coaching activities in the cottage and learning activities. Because the research was carried out during a pandemic, researchers also examined learning activities, learning methods, learning coaching and also coaching constraints during a pandemic situation. The data obtained were then collected and then analyzed and concluded as a statement. The results of this study are that this boarding school includes a new Islamic boarding school but the progress is quite good and at An-Nur Islamic Boarding School it also has different characteristics, namely that it has implemented modern rules. In a pandemic situation, this lodge changed the schedule of activities, which was originally a full day to be advanced earlier, the activities were still carried out well. Thus, the boarding school students have done offline learning because the distance between the hostel and the school is close to each other.